Diagnosis and treatment of inherited thrombocytopenias. Issue 2 (20th May 2015) - Pecci, A.
Abstract : Knowledge in the field of inherited thrombocytopenias (ITs) has greatly improved over the last 15 years. Several new genes responsible for thrombocytopenia have been identified leading to the definition of novel nosographic entities and to a much better characterization of the phenotypes of these diseases. To date, ITs encompass 22 disorders caused by mutations in 24 genes and characterized by different degrees of complexity and great variability in prognosis. Making a definite diagnosis is important for setting an appropriate follow‐up, choosing the best treatments and providing proper counseling. Despite the abovementioned progress, diagnosis of ITs remains difficult and these disorders are still underdiagnosed. The purpose of this review is to provide an updated guide to the diagnosis of ITs based on simple procedures. Moreover, the currently available therapeutic options for these conditions are recapitulated and discussed.